JOB ACCOMPLISHMENT THROUGH INFORMATION TECHNOLOGY COMPETENCIES AND CORPORATE SOCIAL MEDIA USAGE OF COMPANY EMPLOYEES IN INDONESIA - Siti Mujanah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2022)
This research aimed to examine the factors that could affect the distribution of jobs accomplishment, which was included the distribution of corporate social media, information technologies competencies, and jobs interconnections. This research used the partial least square-structural equation model (PLS-SEM) to test the proposed hypothesis. Participants in this study included 367 respondents as the employees in Indonesia. The data collected in this research used a surveyed approached to get responses from participants. The results of data analysis in this research revealed that corporate social media had a significant direct effect on jobs accomplishment and jobs interconnections. In addition, the information technologies competencies had also showed to have an essential direct role in jobs accomplishment and jobs interconnections. Jobs interconnections had also showed to have a significant direct influence on jobs accomplishment. This study proved that jobs interconnections had a significant mediating effect on the relationship between corporate social media and jobs accomplishment, but it had no influencers the relationship between information technologies competencies and jobs accomplishment.